2009
DOI: 10.2478/v10001-009-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine levels in the brain of rats exposed by inhalation to benzalkonium chloride

Abstract: Objectives: The aim of the study was to obtain quantitative data on the effect of inhalation exposure to benzalkonium chloride (BAC) on the concentration of catecholamines and their metabolites in selected brain structures. Additionally, concentration of corticosterone (CORT) in plasma was estimated. Material and Methods: Wistar rats were subjected to a single (6-hour) or repeated (3 days, 6 h/day) exposure to BAC aerosol at ca. 30 mg/m 3 . The Waters integrated analytical system of HPLC was used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In an inhalation study performed in mice, it was found that inhalation of BAC at higher concentrations induced deep lung effects and also lung inflammation [25]. In previous years we assessed toxic effects of BAC to the respiratory system and changes in the concentrations of catecholamines in the brain of rats exposed by inhalation to BAC aerosol [26,27]. The present study is an extension of our earlier works assessing the toxic effects of exposure to aerosol of BAC water solution in laboratory animals under conditions of repeated inhalation exposure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an inhalation study performed in mice, it was found that inhalation of BAC at higher concentrations induced deep lung effects and also lung inflammation [25]. In previous years we assessed toxic effects of BAC to the respiratory system and changes in the concentrations of catecholamines in the brain of rats exposed by inhalation to BAC aerosol [26,27]. The present study is an extension of our earlier works assessing the toxic effects of exposure to aerosol of BAC water solution in laboratory animals under conditions of repeated inhalation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous works have been published describing the toxic activity of BAC in the in vitro and in vivo studies [1][2][3][4][5][6][7][8][9][10][11][12][13]. Scientific interest in BAC toxicity to the living organisms has resulted from a wide range of its use as a bactericide and preservative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress response consists in releasing key peripheral mediators such as catecholamines and glucocorticoids the role of which in the pathophysiology of chronic stress is extraordinarily complex and controversial (4). Moreover, in cancer, catecholamines can enhance carcinogenic properties of prostate, ovary, breast and colon tumor cells (5), while glucocorticoids are immune-suppressive agents (6). It has been reported that the immune system plays an important role in the development of cancer (7)(8)(9).…”
mentioning
confidence: 99%